Compositional and topological determinants of a physiological Ashwell–Morell receptor ligand - John Hintze; Robert Fraumeni; Noortje de Haan; Rebecca L. Miller; Mayank Saraswat; Zhang Yang; Henrik Clausen; Jamey D. Marth (Proceedings of the National Academy of Sciences, 2025)
The hepatocyte Ashwell–Morell receptor (AMR) is the prototypical mammalian lectin and the first cell receptor isolated. This recycling endocytic receptor of the plasma membrane determines the concentrations of hundreds of circulating glycoproteins in the blood and plays important roles in host responses to and outcomes of infection. The compositional and topological determinants of a physiological AMR ligand have remained unclear with contradictory findings reported. Previous studies established that the AMR binds multivalent galactose on desialylated triantennary or higher-branched N-glycans with little to no binding to galactose on biantennary forms. However, the vast majority of circulating blood glycoproteins are modified by biantennary N-glycans, rendering them unlikely to be ligands bound and eliminated by the AMR. Separately, other studies reported that AMR ligands include sialylated N-glycans, and specifically α2-6, but not α2-3, sialic acid linkages. Herein, we investigated the composition and topology of AMR ligands using a known physiological AMR ligand, intestinal alkaline phosphatase (IAP). Recombinant active IAP was produced in glycoengineered cells with either biantennary or higher valency triantennary and tetra-antennary N-glycan structures, and further with and without either α2-6 or α2-3 sialic acid linkages. These closely homogenous IAP monomer glycoforms assemble as dimers with similar enzymatic activity and were compared in AMR binding and clearance assays. Our results indicate that the AMR does not significantly bind IAP when its N-glycans are predominantly sialylated with either α2-6 or α2-3 sialic acid linkages. Multivalent desialylated AMR ligands may, however, appear when IAP monomers dimerize, resulting in the close proximation of biantennary N-glycans.